THE EFFECT OF VILLAGE OFFICIALS’ DIGITAL LITERACY AND SOCIAL MEDIA TRANSPARENCY ON DIGITAL FRAUD PREVENTION IN VILLAGE FUND GOVERNANCE - Bambang Arianto; Gema Ika Sari (Soedirman Accounting, Auditing and Public Sector Journal, 2026)
This study aims to examine the effect of village officials’ digital literacy and social media transparency on digital fraud prevention in village fund governance. In the context of village government, digital fraud may arise from the misuse of information systems, manipulation of financial data, lack of budget information disclosure, and weak technology-based supervision. Village officials’ digital literacy is an important factor that enables village officials to use digital technology appropriately in the process of village financial governance. In addition, social media transparency also serves as a means of public information disclosure that can strengthen community oversight of village fund management. This study employs a quantitative approach using a survey method involving 43 respondents who are related to village financial governance. The research data were analyzed using multiple linear regression or Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the relationships among variables as well as the validity and reliability of the research instruments. The findings reveal that village officials’ digital literacy and social media transparency each have a significant effect on digital fraud prevention in village fund governance. Furthermore, village officials’ digital literacy and social media transparency have a positive effect on digital fraud prevention in village fund governance.